Characterization of dual‐junction III‐V on Si tandem solar cells with 23.7% efficiency under low concentration. (2nd April 2019) - Veinberg‐Vidal, Elias; Vauche, Laura; Medjoubi, Karim; Weick, Clément; Besançon, Claire; Garcia‐Linares, Pablo; Datas, Alejandro; Kaminski‐Cachopo, Anne; Voarino, Philippe; Mur, Pierre; Decobert, Jean; Dupré, Cécilia
Abstract: Monolithic two‐terminal III‐V on Si dual‐junction solar cells, designed for low concentration applications, were fabricated by means of surface‐activated direct wafer bonding. The III‐V top cell is a heterojunction formed by an n‐Ga0.5 In0.5 P emitter and a p‐Al0.2 Ga0.8 As base. An efficiency of 21.1 ± 1.5% at one sun and 23.7 ± 1.7% at 10 suns is demonstrated, which to our knowledge is the best dual‐junction two‐terminal III‐V on Si tandem cell efficiency reported to date under verified reference conditions. The I‐V characterization of these 1‐cm 2 tandem cells under concentration required the development of a new method using a single‐source multiflash solar simulator and not perfectly matched component cells, also known as pseudo‐isotypes, formed by Si single‐junction cells and optical filters. In addition, the spectrum of the pulsed solar simulator was measured using a high‐speed CMOS spectrometer, allowing the calculation of the spectral mismatch correction factor. Merging these two techniques results in the hybrid corrected pseudo‐isotype (HCPI) characterization method, which shows a fast and accurate performance with a simplified procedure based on a single‐source solar simulator. Pseudo‐isotypes are easily adaptable to new cell designs by simply using a different filter, hence allowing the characterization of new multijunction solar cell architectures. Abstract : Monolithic two‐terminal (2 T) III‐V on Si dual‐junction (2 J) solar cells, designed for low concentration applications, were fabricated by means of surface‐activated bonding (SAB). An efficiency of 21.1 ± 1.5% at one sun and 23.7 ± 1.7% at 10 suns is demonstrated, which is the best 2 J 2 T III‐V on Si tandem cell efficiency reported to date under verified reference conditions. The I‐V characterization required the development of a new method using a single‐source multiflash solar simulator and not perfectly matched component cells, also known as pseudo‐isotypes.